2022
DOI: 10.14444/8205
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Intraoperative Neurophysiological Monitoring Rates for Anterior Cervical Discectomy and Fusion: Are Diagnostic or Procedural Codes Accurate?

Abstract: Background: The utility of intraoperative neurophysiological monitoring (IONM) is well established for some spine surgeries (eg, intramedullary tumor resection, scoliosis deformity correction), but its benefit for most degenerative spine surgery, including anterior cervical discectomy and fusion (ACDF), remains debated. National datasets provide "big data" approaches to study the impact of IONM on spine surgery outcomes; however, if administrative coding in these datasets misrepresents actual IONM usage, concl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…In our study, neurological deficits were found in only 0.6% (210 out of 34,592 patients). One study investigated the IONM coding accuracy in cervical spine surgery with the NIS database and reported that ICD coding underestimated IONM usage, whereas Current Procedural Terminology (CPT) coding was more accurate 33 . That study concluded that currently, available national databases based on administrative codes do not accurately reflect IONM usage 33 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, neurological deficits were found in only 0.6% (210 out of 34,592 patients). One study investigated the IONM coding accuracy in cervical spine surgery with the NIS database and reported that ICD coding underestimated IONM usage, whereas Current Procedural Terminology (CPT) coding was more accurate 33 . That study concluded that currently, available national databases based on administrative codes do not accurately reflect IONM usage 33 .…”
Section: Discussionmentioning
confidence: 99%
“…One study investigated the IONM coding accuracy in cervical spine surgery with the NIS database and reported that ICD coding underestimated IONM usage, whereas Current Procedural Terminology (CPT) coding was more accurate. 33 That study concluded that currently, available national databases based on administrative codes do not accurately reflect IONM usage. 33 Since our study used ICD codes for IONM, the neurological deficit rate may In our study results, neither neurological deficits nor LOS showed a difference between the IONM and non-IONM groups.…”
Section: Epidemiologymentioning
confidence: 98%
See 1 more Smart Citation
“…In the NIS and NSQIP databases, IONM utilization varied widely from 0.76% to 18.4%, respectively. 28 The implication is that national databases and SPARCS may be unequipped to fully understand the utilization of IONM. It is unclear if IONM alerts significantly affect real-time clinical decision-making during ACDF surgery to prevent neurological injury and postoperative deficit.…”
Section: Intraoperative Neuromonitoring Utilizationmentioning
confidence: 99%
“…5 Moreover, while billing data containing codes from the International Classification of Diseases and Current Procedural Terminology might also seem to provide readily available structured data sets, these similarly often lack specific clinical parameters of interest or fail to adequately identify performed procedures. 6-8…”
mentioning
confidence: 99%